Heterogeneous reduction of carbon dioxide by hydride-terminated silicon nanocrystals - Wei Sun (Nature Portfolio, 2016)
Elemental silicon is widely studied for photovoltaic applications. Here, the authors report that hydride-terminated silicon nanocrystals can also function as single component heterogeneous reducing agent for converting gaseous carbon dioxide selectively to carbon monoxide.